Теоретичні аспекти пошуку раціонального плану розвитку будівельної організації із застосуванням комбінаторної оптимізації - Доненко, В. І.; Антипенко, Є. Ю.; Доненко, І. В.; Ярова, Л. В. (Ways to Improve Construction Efficiency, 2012)
The paper shows a heuristic algorithm for finding an optimal sequence of development work’s areas in the flow with the critical paths and identified resource and front ties.